Genetic and Environmental Factors in Parkinson's Disease Converge on Immune Function and Inflammation. Issue 1 (14th December 2020) - Kline, Elizabeth M.; Houser, Madelyn C.; Herrick, Mary K.; Seibler, Philip; Klein, Christine; West, Andrew; Tansey, Malú G.
Abstract: Idiopathic Parkinson's disease (iPD) is a movement disorder characterized by the degeneration of dopaminergic neurons and aggregation of the protein α‐synuclein. Patients with iPD vary in age of symptom onset, rate of progression, severity of motor and non‐motor symptoms, and extent of central and peripheral inflammation. Genetic and environmental factors are believed to act synergistically in iPD pathogenesis. We propose that environmental factors (pesticides and infections) increase the risk for iPD via the immune system and that the role of PD risk genes in immune cells is worthy of investigation. This review highlights the major PD‐relevant genes expressed in immune cells and key environmental factors that activate immune cells and, alone or in combination with other factors, may contribute to iPD pathogenesis. By reviewing these interactions, we seek to enable the future development of immunomodulatory approaches to prevent or delay onset of iPD. © 2020 International Parkinson and Movement Disorder Society